Peningkatan Produktivitas Dalam Rangka Mewujudkan Pekerjaan Layak dan Pertumbuhan Ekonomi (Tujuan ke-8 Sustainable Development Goals) - Ponto, Vivi Marietha (Cendekia Niaga, 2023)
Sustainable development accommodates economic, social and environmental aspects simultaneously. There are three elements that must be harmonized to achieve sustainable development, namely economic growth, social inclusion and environmental protection. Decent work and economic growth are among the goals of the SDGs needed to restore Indonesia's economy which was eroded by the Covid-19 pandemic crisis. To recover the Indonesian economy, it needs to be supported by the effective and efficient use of resources. This is intended to increase produc.tivity which will accelerate Indonesia's economic growth. This article examines the link between increasing productivity and realizing decent work and economic growth, which is the 8th goal of the Sustainable Development Goals. Decent work is supported by decent wages and other things that support the welfare of workers provided by the employer (employer). If this is done by the employer then worker productivity will increase. Thus, worker productivity will encourage the production of goods and services which in turn can drive economic growth.